DIGITAL-BASED LOCAL HISTORY INTEGRATION IN HISTORY LEARNING AT PALEMBANG HIGH SCHOOL: Integrasi Sejarah Lokal Berbasis Digital dalam Pembelajaran Sejarah di SMA Palembang - Sukardi; Gunarhadi; Djono (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2025)
This study discusses the integration of digital-based local history in history learning in Palembang high schools with a focus on the readiness and obstacles faced by teachers. Digital transformation in history education is expected to improve students' understanding of local history and adapt the learning process to technological developments. This study uses a qualitative descriptive approach with data collection methods through interviews, observations, and distributing questionnaires to history teachers in several high schools in Palembang. The results of the study show that most teachers are aware of the importance of implementing digital technology in history learning, but there are still differences in their level of readiness. Factors that support teacher readiness include basic skills in using technology and school support. Meanwhile, the main obstacles faced include limited technological infrastructure, lack of technical training, minimal digital learning resources based on local history, and limited time in implementing the curriculum. In addition, resistance to changes in learning methods is also a challenge in this integration process. The conclusion of this study emphasizes the need to improve teachers' digital competence through continuous training, development of adequate digital resources, and support from schools and related stakeholders. With these steps, digital-based local history integration can be an effective strategy in improving students' historical literacy and strengthening their awareness of local history.